2022
DOI: 10.1136/bmjopen-2021-056193
|View full text |Cite
|
Sign up to set email alerts
|

Identifying self-report measures of emotion regulation and evaluating their psychometric properties: a protocol for a systematic review

Abstract: IntroductionSuccessful emotion regulation (ER) is critical for psychological health. Disturbances in this ability are associated with several psychiatric disorders. There are several self-report questionnaires to assess ER. However, there are no studies synthesising the evidence on their psychometric properties. We aim to identify all available instruments addressing ER in adolescents or adults and to critically appraise, compare and summarise the quality of their psychometric properties. For this, we will use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Despite an increasing effort to unite coping and emotion regulation from a conceptual standpoint (Compas et al, 2014; Stanisławski, 2019; Troy et al, 2023), virtually all reviews of their self-reported measures have been led in parallel, which limits the appreciation of similarities and distinctions. Among those reviewed, most validated scales focused on strategies typically used, as a disposition (trait like), by nonclinical adult samples (Greenaway et al, 2014; Kato, 2015; Núñez et al, 2022; Penley et al, 2002; Zaid et al, 2021). Besides, a growing field is emerging on intensive longitudinal assessment methodologies that permit a better consideration of the contexts in which such strategies are implemented (i.e., in-the-moment coping/emotion regulation; state like), with most reviews targeting emotion regulation (Boemo et al, 2022; Schatten et al, 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite an increasing effort to unite coping and emotion regulation from a conceptual standpoint (Compas et al, 2014; Stanisławski, 2019; Troy et al, 2023), virtually all reviews of their self-reported measures have been led in parallel, which limits the appreciation of similarities and distinctions. Among those reviewed, most validated scales focused on strategies typically used, as a disposition (trait like), by nonclinical adult samples (Greenaway et al, 2014; Kato, 2015; Núñez et al, 2022; Penley et al, 2002; Zaid et al, 2021). Besides, a growing field is emerging on intensive longitudinal assessment methodologies that permit a better consideration of the contexts in which such strategies are implemented (i.e., in-the-moment coping/emotion regulation; state like), with most reviews targeting emotion regulation (Boemo et al, 2022; Schatten et al, 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Relevant data from each retained article was then extracted (Stage 4). As done in prior reviews (Núñez et al, 2022; Zaid et al, 2021) and suggested elsewhere (Arksey & O’Malley, 2005; Peters et al, 2015), we coded the following elements for each coping and emotion regulation measure: name, year of publication, country of study completion, structure of the measure (e.g., construct evaluated, number of items, strategies covered, time frame, context, and response options), sample characteristics, and psychometric properties. As psychometric properties, we retained internal consistency for multi-item validated scales and intraclass correlations (ICC) for the intensive longitudinal assessments, as they were the ones available for most measures.…”
Section: Scoping Review Protocolmentioning
confidence: 99%
See 1 more Smart Citation